89.6k views
5 votes
Solve. X2 - x-6=0
{3, -2)
{6, -1}
(12, -3}
(- 2, -3)

2 Answers

6 votes

Answer:

below

Explanation:


x^(2) - x - 6 = 0 is a quadratic equation so we will use the quadratic formula


a = 1 \\b = -1 \\c = -6

the quadratic formula is
b^(2) - 4ac


  • b^(2) - 4ac = (-1)²- 4*(1)*(-6) = 25
  • 25 is a positive value so the equation has two solutions


x = (-b - / + √(25) )/(2a)
(1 -/+ 5)/(2)


x = -2 \\x = 3

Solve. X2 - x-6=0 {3, -2) {6, -1} (12, -3} (- 2, -3)-example-1
4 votes

Answer:

-2, 3

Explanation:


x^2-x-6=0

Factoring:


(x-3)(x+2)=0


\therefore x=3 \text{ or } x=-2

User Emptyflash
by
5.0k points